A Brief Study on AES Technique With Double and Triple Block Cipher - Devi, P. Lakshmi; Reddy, K. Madhusudhan (International Journal of Computer Sciences and Engineering, 2025)
Cryptography plays an important role in data security. During digital exchange of data, it is important; data should not be access by an unauthorized user. Cryptography methods are based on symmetric and asymmetric encryption. It is challenging researchers to find out advanced encryption security development algorithm. Cryptography techniques are based on, symmetric key or private key and asymmetric key or public key. Researchers worked on secure and efficient data transmission and presented various cryptographic techniques. For secure and efficient data transmission over the network, it is necessary to use correct encryption method. Symmetric encryption is widely used technique. In this research work, we are presenting an efficient block cipher encryption techniques based on triple method and improved key. Proposed AESD method is based on block level symmetric encryption. The proposed AESD method is based on improve cubes. A pair of binary inputs are contains by each cell. The Cube can able to provide a various number of combinations, by that system will generate a strong cipher text. For efficient and strong cipher, proposed technique uses shuffling of bits in cube. Proposed AESD algorithm, performed a series of bit transformations, by using of S-BOX, operation XOR, and operation AND. The performance analysis of proposed encryption technique are compared with different existing symmetric encryptions methods, based on block cipher encryption, such as Data encryption standard, 3-Data encryption standard, Advance encryption standard, and blowfish fish, based on various comparison parameters such as encryption and decryption time, Avalanche effect and cipher text size. Simulation results clearly shows that proposed method performs outstanding in terms of encryption and decryption time, Avalanche effect and size, as compared to existing methods.